Penerapan Metode Promethee Pada Sistem Pendukung Keputusan Dalam Pemilihan Kepala Sekolah Pada SMK Swasta Nurul Amaliyah Tanjung Morawa - Delfiana Sihite (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
School is a building or institution for learning and teaching as well as a place to give and receive lessons. Each school is led by a principal, and the principal is assisted by his deputy. Basically, every agency must have a leader to lead and manage an organization/agency so that the agency can run well and be useful for the state and society. School progress cannot be separated from the influence of the ability of the leader or principal in managing all the resources that exist in the school. The selection of the principal is very important for Nurul Amaliyah Private Vocational School because the principal is the highest leader who is very influential on the progress of the school. However, at the Nurul Amaliyah Private Vocational School, the principals were chosen inefficiently because most of those elected did not meet certain requirements. So that the process of selecting the principal of Nurul Amaliyah Private Vocational School did not go well and did not meet expectations. One way to overcome the election of school principals is by implementing a decision support system. The application of a decision support system in the selection of school principals is very influential because the application of the SPK can make it easier for schools to select school principals according to predetermined criteria. To make it easier to solve this problem using a method. The method that is suitable for use is the Promethee method, because the calculation is carried out in several stages and ranking, where the process is carried out by comparing in detail the value of one candidate with another so that the results are quite accurate. Promethee is a sequencing method in multi-criteria analysis, simplicity, clarity and stability. The use of scores in the outranking relationship is presumed in that this is a ranking method that is quite simple in concept and application compared to other methods for multicriteria analysis. With the application of the Promethee method, it can help in selecting the right school principal, because the calculation is done in several stages and ranking, where the process is done by comparing in detail the value of one candidate with another so that the results are quite accurate.